ANALISIS PENGARUH FAKTOR-FAKTOR DIMENSI KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH KSPPS UBASYADA CIPUTAT DENGAN MENGGUNAKAN ANALISIS REGRESI LOGISTIK BINER - Siti Nuur Rokhmah; Besse Arnawisuda Ningsi (LPPM Universitas Bina Bangsa, 2023)
Ubasyada Ciputat Sharia Savings and Loans and Financing Cooperative (KSPPS) is a cooperative whose business activities are engaged in savings and loans as the principal of its business, as well as funding, financing, and also food stalls. The results of preliminary studies show that there is a lack of interest in people living around to become cooperative customers. This study aims to determine the influence of service quality dimension factors on customer satisfaction of Ubasyada Ciputat Sharia Savings and Loans and Financing Cooperative (KSPPS) using binary logistic regression analysis. The population and sample as of this writing are 30 priority customers of the Ubasyada Ciputat Savings and Loans and Sharia Financing Cooperative (KSPPS). Data is obtained by distributing questionnaires to customers, then tested for validation and reliability and then carried out Binary Logistic Regression tests. From the results of the analysis, it was obtained that the influence of service quality dimension factors that most influence customer satisfaction of Ubasyada Ciputat Savings and Loans and Sharia Financing Cooperative (KSPPS), namely assurance (X4) and empathy (X5) have a positive effect on customer satisfaction (Y).